Transformative Learning on the Desert’s Edge: The Tostan FGM Program in Senegal, Mali and the Sudan - Peter Easton; Kristen Molyneaux (Adult Education Research Conference, 2006)
This paper examines strategies of the Tostan Village Empowerment Program in Senegal for promoting abandonment of female genital mutilation as an example of transformative learning; and it draws lessons for the refinement of that theory.
Keywords: Empowerment; transformative learning; female genital mutilation